Nilai-Nilai Budaya Dalam Lagu Ndas Gerih Karya Denny Caknan; Studi Semiotika Ferdinand De Saussure - Ma'rufi, Ilham; Ardi, Mulia (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Denny Setiawan or Denny Caknan is classified as successful in inspiring millennial generation to be culturally literate through their musical works with regional nuances. Denny became known to the public when his song Kartonyono Medhot Janji went viral in 2019. At the end of 2020 Denny released a new song entitled Ndas Gerih. This song is unique because the song lyrics are written in 3 languages, namely Javanese, Indonesian and English, with more than 30 million views and 27 thousand comments. Not only that, the visualization in the video clip of the song is rich of local cultural and traditional values. This study specifically aims to analyze the cultural values in the Ndas Gerih song through the semiotic perspective of Ferdinand De Saussure. This research is a qualitative descriptive research with the objects of this research, namely lyrics, music (audio) and pictures. The results showed that cultural values were represented in each of the lyrics, music and video clips of the Ndas Gerih song. Those values are local traditional values, religious value, aesthetic value and economic value.